Brolucizumab: the road ahead - Sharma, Ashish; Kumar, Nilesh; Bandello, Francesco; Kuppermann, Baruch D; Loewenstein, Anat; Regillo, Carl D (British journal of ophthalmology, 2020)
Correspondence to Ashish Sharma, Lotus Eye Hospital and Institute, Avinashi Road, Civil Aerodrome Post, Peelamedu, Coimbatore, Tamil Nadu 641014, India; drashish79@hotmail.com The management and outcome of retinal disorders was revolutionised with the advent of ocular anti-vascular endothelial growth factor (VEGF) therapies including US Food and Drug Administration (FDA)-approved ranibizumab (Lucentis; Genentech, South San Francisco, CA, USA) and aflibercept (Eylea; Regeneron, Tarrytown, NY, USA) and off-label bevacizumab (Avastin; Genentech). 1 The real-world studies though have highlighted a few restrictions to the approved regimens, primarily the required monthly injections and follow-up visits. 2 Multiple treatment regimens have been introduced in recent years to reduce the frequency of anti-VEGF agent dosing while attempting to maintain efficacy comparable to monthly or bimonthly fixed treatment protocols by individualising therapy. Based on the clinical trial data from HAWK and HARRIER, brolucizumab demonstrated superior anatomic results with greater fluid resolution and similar best-corrected visual acuity compared to aflibercept with the possibility to extend the dosing regimen to q12-week intervals potentially reducing treatment burden. 4 Brolucizumab is the first humanised single-chain antibody fragment to be approved for therapeutic use across the field of medicine. Earlier trials such as Comparision of Age-Related Macular Degeneration Treatment Trials (CATT) and Efficacy and Safety of Ranibizumab in Subjects with Subfoveal and CNV secondary to AMD (EXCITE) have demonstrated that the presence of IRF is an indicator of a later decline in visual acuity. 8 The better control of IRF with brolucizumab might have contributed to the >50% proportion of patients maintaining q12w dosing through 1 year of follow-up. 4 The FDA has approved a q8/q12 dosing schedule for the molecule after three monthly loading doses.